Crystal structure of dodecalanthanum heptadecaiodide triethanide, La12I17(C2)3 - Mattausch Hj.; Simon A. (Zeitschrift für Kristallographie - New Crystal Structures, 2005)
C6I17La12, monoclinic, C12/c1 (no. 15), a = 19.927(1) Å, b = 12.636(1) Å, c = 19.399(1) Å, β = 90.24(1)°, V = 4884.6 Å3, Z = 4, Rgt(F) = 0.026, wRref(F2) = 0.062, T = 293 K.